2020
DOI: 10.1016/j.rmed.2020.105996
|View full text |Cite
|
Sign up to set email alerts
|

Severe respiratory SARS-CoV2 infection: Does ACE2 receptor matter?

Abstract: SARS-CoV-2 is a novel virus of the Coronaviridiae family that represents a major global health issue. Mechanisms implicated in virus/host cells interaction are central for cell infection and replication that in turn lead to disease onset and local damage. To enter airway and lung epithelia, SARS-CoV-2 attaches to ACE2 receptors by spike (S) glycoproteins. Molecular mechanisms that promote interaction between SARS-CoV-2 virus and host with particular focus on virus cell entry receptor ACE2 are described. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 51 publications
(61 reference statements)
5
168
0
3
Order By: Relevance
“… 75 , 76 Many of the HPB suppressors affect ACE2 gene expression in a tissue-specific manner. 77 79 To the best of our knowledge, no experimental result has been published about the effect of ACE2-specific drugs on the affinity of ACE2 for S1 of SARS-CoV-2. Some studies reported the effect of binding of some molecules to ACE2 in the closed conformation on the affinity of ACE2 for the SARS spike.…”
Section: Resultsmentioning
confidence: 99%
“… 75 , 76 Many of the HPB suppressors affect ACE2 gene expression in a tissue-specific manner. 77 79 To the best of our knowledge, no experimental result has been published about the effect of ACE2-specific drugs on the affinity of ACE2 for S1 of SARS-CoV-2. Some studies reported the effect of binding of some molecules to ACE2 in the closed conformation on the affinity of ACE2 for the SARS spike.…”
Section: Resultsmentioning
confidence: 99%
“…Its most recognized activity is inhibition of Na,K-ATPase through blockade of ATP binding sites. Other membrane-positioned enzymes requiring ATP include ACE-2 which has now been shown to be an entry receptor for SARS-CoV-2 (22). The potential role of oleandrin as an active principle ingredient in the botanical drug (PBI-05204) designed to treat malignant disease has been reported (12)(13)(14)19).…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies reported that, although not directly affecting ACE2 activity, these drugs are able to upregulate its expression (Ishiyama et al, 2004;Ferrario et al, 2005;Gallagher et al, 2008). Increased expression of ACE2 has also been reported to facilitate SARS-CoV infection in several experimental models and postulated to act in the same way for SARS-CoV-2 (Li et al, 2003;Hofmann et al, 2004;Perrotta et al, 2020).…”
Section: The Controversial Role Of Ace2 Expressionmentioning
confidence: 99%